Central amygdala angiotensin type 1 receptor (Agtr1) expressing neurons contribute to fear extinction. (15th May 2023) - Yu, Zhe; Kisner, Alexandre; Bhatt, Amy; Polter, Abigail M.; Marvar, Paul J.
Abstract: The renin-angiotensin system (RAS) has been linked to the pathophysiology of posttraumatic stress disorder (PTSD) however, the underlying neurobiological mechanism(s) remain elusive. Here we utilized angiotensin II receptor type 1 (AT1 R) transgenic mice combined with neuroanatomical, behavioral, and electrophysiological approaches, to examine the role of the central amygdala (CeA) expressing AT1 R neurons in fear and anxiety-related behavior. Within the major amygdala subdivisions, AT1 R + neurons were localized to gamma-aminobutyric acid (GABA) expressing neurons in the lateral division of the central amygdala (CeL), and the majority of them were identified as protein kinase C-δ positive (PKCδ + ) neurons. Following CeA-AT1 R deletion using cre-expressing lentiviral delivery in AT1 R-Flox mice, generalized anxiety and locomotor activity as well as the acquisition of conditioned fear were unaltered while the acquisition of extinction learning, as measured by percent freezing behavior, was significantly enhanced. During electrophysiological recordings of CeL-AT1 R + neurons, the application of angiotensin II (1 μm) increased the amplitude of spontaneous inhibitory postsynaptic currents (sIPSCs) and decreased the excitability of CeL-AT1 R + neurons. Overall, these findings demonstrate that CeL-AT1 R-expressing neurons play a role in fear extinction, potentially through facilitated CeL-AT1 R + GABAergic inhibition. These results provide new evidence for mechanisms of angiotensinergic neuromodulation of the CeL and its role in fear extinction and may aid in further advancing targeted novel therapies for improving maladaptive fear learning processes associated with PTSD. Highlights: Agtr1a is uniquely expressed in mouse CeL compared to other amygdala subnuclei. CeL- Agtr1a contributes to the quicker acquisition of extinction learning. CeL-Agtr1a positive neurons predominately co-localize with previously identified PKCδ+ CeLoff neurons. AT1R activation with angiotensin II increases GABAergic inhibition in CeL-Agtr1a + neurons.